Pediatric Emergency Cases in the First Year of the COVID-19 Pandemic in a Tertiary-Level Emergency Setting - Cozzi, Giorgio; Molina Ruiz, Idoya; Giudici, Fabiola; Romano, Sara; Grigoletto, Veronica; Barbi, Egidio; Amaddeo, Alessandro (Frontiers in Pediatrics, 2022)
Aim Emergency cases are uncommon events in the pediatric emergency setting. This study aimed to evaluate the effect of the Coronavirus disease 2019 (COVID-19) pandemic by describing the number and type of pediatric emergency cases that arrived at the pediatric emergency department (PED) of a tertiary-level children’s hospital in Italy. Methods We performed a retrospective study, collecting the main features of pediatric emergency patients who arrived during the first year of the COVID-19 pandemic (March 2020–February 2021) compared to the pre-pandemic period (March 2016–February 2020). Results During the study period, 112,168 patients were visited at the PED, and 237 (0.21%) were emergency cases, median age of 4 years (IQR: 1–12). In the first year of the pandemic, 42 children were coded as emergency cases compared to 195 (49/year) during the pre-pandemic period. The proportion of emergency cases was stable (0.27% during the COVID-19 period versus 0.20% during the pre-COVID-19 period, p = 0.19). No differences were found regarding the age, gender, hour of arrival, and outcome of patients. We found a significant decrease in the proportion of emergency cases related to respiratory diseases (9/42, 21.4% during the COVID-19 period versus 83/195 during the pre-COVID-19 period (42.6%), p = 0.01). Conclusion In conclusion, our data suggest that the pandemic had a more significant impact on respiratory emergency cases than on pediatric emergencies in general.